2022
DOI: 10.3390/ijms23105611
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Improves Lipid Dysregulation by Modulating Circadian Genes Bmal1 and Clock in HepG2 Cells

Abstract: Metabolic disorders are closely associated with the dysregulation of circadian rhythms. Many bioactive components with lipid metabolism-regulating effects have been reported to function through circadian clock-related mechanisms. As the main pungent principle of black pepper, piperine (PIP) has been demonstrated to possess anti-obesity bioactivity by affecting hepatic lipid metabolism-related factors. However, whether the circadian clock genes Bmal1 and Clock are involved in the protective effect of PIP agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Further and deeper research needs to be performed in order to find new approaches for ameliorating metabolic disorders by targeting biological clock and circadian synchronization. Recent research conducted in vitro on cultured hepatocytes showed that BMAL1 and CLOCK play an important role in the regulation of hepatic lipid homeostasis by modulating the SREBP1c/PPARγ signaling pathway [26], confirming the significant role of circadian rhythm in MASLD development and progression [27][28][29].…”
Section: The Role Of the Circadian Clock In Insulin Resistance And Ma...mentioning
confidence: 84%
“…Further and deeper research needs to be performed in order to find new approaches for ameliorating metabolic disorders by targeting biological clock and circadian synchronization. Recent research conducted in vitro on cultured hepatocytes showed that BMAL1 and CLOCK play an important role in the regulation of hepatic lipid homeostasis by modulating the SREBP1c/PPARγ signaling pathway [26], confirming the significant role of circadian rhythm in MASLD development and progression [27][28][29].…”
Section: The Role Of the Circadian Clock In Insulin Resistance And Ma...mentioning
confidence: 84%
“…It has been observed that abnormalities in circadian rhythm genes are directly connected with metabolic disruption [ 32 , 33 ]. The protein-to-protein interaction network for Clock, Bmal1 (ARNTL), and other circadian rhythm genes from STRING protein database ( , accessed on 6 September 2022) is shown in Figure 3 F. The hepatic expression Clock and Bmal1 proteins by Western blot were remarkably decreased in the MAFLD group, which can be significantly increased with the BBR treatment ( p < 0.05) in Figure 2 I,J.…”
Section: Resultsmentioning
confidence: 99%
“…Piperine (PIP) found in large quantities in Piper nigrum L. that has anti-obesity, anti-inflammatory, and hepatoprotective properties ( Cheng et al, 2023 ; Joshi et al, 2023 ). In vitro studies have found that PIP regulates lipid metabolism in HepG2 cells in a Bmal1/Clock-dependent manner ( Zhang et al, 2022 ) and in vivo studies have found that PIP ameliorates insulin resistance in diabetic mice constructed by subcutaneous injection of monosodium glutamate (MSG) in neonatal mice ( Liu et al, 2020 ). Piperine was administered at 20 and 40 mg/kg body weight per day in an obese mouse model induced by high-fat dietary feeding.…”
Section: Role Of Natural Products and Their Extracts In Fatty Liver D...mentioning
confidence: 99%